Formarte : una aproximación pedagógica a la evaluación formativa en el ITIF (2017)
This work reports on the process carried out by three teachers from The Instituto Técnico Industrial in Facatativá city, in their efforts to generate significant changes in the teaching practice with the aim of implementing some academic resources, that allow to approach the formative assessment in the Physics subject. A qualitative method was carried out, framed within the model proposed by "Skosmovse and Borba" called Critical Investigation "(2004)". It addresses the practice of the physics teacher in The Degree 10-03 and the how through the implementation of these resources such as rubrics, modeling and collaborative work; processes were generated, allowing to develop an authentic evaluation and in this way to lay foundation that initiates a formative evaluation in our institution. Throughout the process, the research group: designed, constructed, piloted, and validated the various instruments used by students, such as: aligned assessments, rubrics, workshops, and quarterly plans, as well as the development of a portfolio, which allowed them to generate elements, tending to be able to bring about a self-assessment and a reflexive and critical evaluation. Finally, after having carried out the different activities proposed in the present research exercise, a transformation of the pedagogical practice was achieved as the class moved from being teacher-centered to focusing on students, generating processes that involved learning experiential on the other hand, with the design and implementation of instruments we achieved initial advances that were fundamental for the development of formative evaluation in the grade mentioned.--Tomado del Formato de Documento de Grado.